P-287 Direct Binding of Autophagy Transcripts via mRNA Binding Protein IMP1. (February 2017) - Hamilton, Kathryn; Chatterji, Priya; Semper, Fernando; Andres, Sarah; Whalen, Kelly; Mizuno, Rei; Lundsmith, Emma; Hicks, Philip; Giroux, Veronique; Tartaglia, Gian; Rusgi, Anil
Abstract : Background: IMP1 (Insulin-like growth factor-2 mRNA binding protein 1) is essential for normal gut development and aberrant overexpression promotes colorectal tumors; however, the role of IMP1 in epithelial homeostasis in the adult intestine remains unclear. We have found that IMP1 loss augments autophagy in the intestinal epithelium during homeostasis and response to injury. Recent studies have linked aberrations in autophagy to Crohn's disease. We therefore sought to evaluate direct binding of IMP1 to autophagy pathway mRNAs. Methods: Published UV-crosslinking and immunoprecipitation (CLIP) experiments for IMP1 were interrogated for binding to autophagy mRNAs. RNP-immunoprecipitation (RIP) assays for putative autophagy targets were performed in Caco2 cells, which express moderate levels of endogenous IMP1. Computational analyses identified specific binding motifs for IMP1 within autophagy mRNA sequences. Results: Based upon published CLIP-Seq data sets, IMP1 binds directly to the following autophagy mRNAs: BECN1, MAP1LC3B, SQSTM1, ATG3. RIP assays in Caco2 cells confirmed these interactions, suggesting that IMP1 may bind and sequester autophagy transcripts under certain conditions. Computational analyses demonstrate confirmation of these interactions and provide a unique binding sequence within these transcripts for IMP1 binding. Conclusions: Our data demonstrate via 3 independent methods that IMP1 binds directly multiple autophagy mRNAs. Taken together with our data that IMP1 loss enhances basal autophagy, our findings suggest that IMP1 may represent a new repressor of autophagy in the gut. Furthermore, identification of the specific sequence for IMP1 binding to autophagy transcripts may provide a foundation for novel therapeutic strategies to enhance autophagy via inhibition of the interaction between IMP1 and autophagy mRNAs.